High levels of serum angiogenic growth factors in patients with AL amyloidosis: Comparisons with normal individuals and multiple myeloma patients - Kastritis, E.; Roussou, M.; Michael, M.; Gavriatopoulou, M.; Michalis, E.; Migkou, M.; Delimpasi, S.; Kyrtsonis, M.C.; Gogos, D.; Liapis, K.; Charitaki, E.; Repousis, P.; et al. (British Journal of Haematology, 2010)
Summary Serum levels of five angiogenic cytokines were evaluated in 82 patients with primary systemic amyloidosis (AL). Angiopoietin-1, vascular endothelial growth factor, basic fibroblast growth factor and angiogenin were higher in AL patients than in controls (n = 35) and newly-diagnosed, symptomatic, myeloma patients (n = 35). Angiopoetin-1/Angiopoetin-2 ratio was lower in AL compared to controls but higher than in myeloma patients. Angiopoetin-2 correlated with cardiac dysfunction indices; however, none of the angiogenic growth factors was prognostically significant. The increased angiogenic cytokine levels observed in AL seem to represent either a toxic effect of amyloid fibrils or light chains, or a compensatory response to organ dysfunction. © 2010 Blackwell Publishing Ltd.
Keywords: amyloidosis; Angiogenesis; angiopoietin; myeloma; Vascular endothelial growth factor